Proyecto de creación de una empresa exportadora de banano hacia la unión europea - Falcones Cevallos, Betty Lissette (2009)
The present study was made with the purpose of analyzing the process of export of banana tree towards the member countries of the European Union giving greater approach to its new members. The activity of the banana tree in Ecuador has had and has an important weight in the development of the country, as much from the economic point of view like social In the economic thing by its approximated participation of the 3,84% of the total GIP in the last years and in the currency generation and the social thing by the sources of use that it generates and still more by their important weight in certain regions of the Ecuadorian coast. Ecuador has advantages like the availability of the product thanks to its climate and fertile earth, also disadvantages like the instability of the prices at world-wide level to be able to carry out agricultural exports. The Ecuadorian banana tree is known by its high quality level, causing that Ecuador is one of the greater exporter of banana tree followed by Costa Rica, the Philippines and Colombia, being the European Union its main importer. This type of exports has given many opportunities him to our country since this occurring to know other products under the Ecuadorian mark.